1989
DOI: 10.4049/jimmunol.143.5.1606
|View full text |Cite
|
Sign up to set email alerts
|

Products of lipopolysaccharide-activated macrophages (tumor necrosis factor-alpha, transforming growth factor-beta) but not lipopolysaccharide modify DNA synthesis by rat trophoblast cells exhibiting the 80-kDa lipopolysaccharide-binding protein.

Abstract: Pregnancy losses from gram negative bacterial infections could be caused by direct effects of LPS on placental cells, or indirectly via LPS activation of macrophages in the uteroplacental unit. To evaluate those alternatives, LPS, LPS-activated peritoneal cells, conditioned medium from LPS-activated peritoneal cells, and some purified and recombinant molecules known to be secreted by activated macrophages were tested for their abilities to modify DNA synthesis by rat trophoblast cells. Three trophoblast cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The anti‐inflammatory properties of pentoxifylline are of particular interest in pre‐eclamptic patients, whom display increased plasma levels of pro‐inflammatory cytokines, including IL‐6 , IFN‐γ and TNF‐α (Jonsson et al, 2006 ; Szarka et al, 2010 ), and suppressed production of IL‐5 and the anti‐inflammatory cytokine IL−10 (Azizieh et al, 2005 ; Szarka et al, 2010 ). This inflammatory response may originate from the pre‐eclamptic placenta (Munno et al, 1999 ) and could subsequently contribute to placental dysfunction, endothelial damage and ischaemic‐reperfusion injury (Hunt et al, 1989 ; Nawroth & Stern, 1986 ; Raghupathy & Raghupathy, 2013 ; Stark, 1993 ). Speer et al ( 2017 ) observed that pentoxifylline reduced LPS‐induced inflammation in an ex vivo placental explant model, often used to study pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…The anti‐inflammatory properties of pentoxifylline are of particular interest in pre‐eclamptic patients, whom display increased plasma levels of pro‐inflammatory cytokines, including IL‐6 , IFN‐γ and TNF‐α (Jonsson et al, 2006 ; Szarka et al, 2010 ), and suppressed production of IL‐5 and the anti‐inflammatory cytokine IL−10 (Azizieh et al, 2005 ; Szarka et al, 2010 ). This inflammatory response may originate from the pre‐eclamptic placenta (Munno et al, 1999 ) and could subsequently contribute to placental dysfunction, endothelial damage and ischaemic‐reperfusion injury (Hunt et al, 1989 ; Nawroth & Stern, 1986 ; Raghupathy & Raghupathy, 2013 ; Stark, 1993 ). Speer et al ( 2017 ) observed that pentoxifylline reduced LPS‐induced inflammation in an ex vivo placental explant model, often used to study pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%